Correlation Between 25-Hydroxyvitamin D Levels ND Preeclampsia among Primigravida Mothers - Keysha Amalia Fitrah Adrian; Agung Sunarko Putra; Dian Ardiana; Mita Herdiyantini (Indonesian Journal of Global Health Research, 2026)
Maternal Mortality Rate (MMR) is still a health challenge at the global and national levels. One of the main causes of maternal mortality is preeclampsia, which can cause serious complications in both the mother and the fetus. Risk factors for preeclampsia include reproductive status, health conditions, and nutritional deficiencies, including vitamin D. Vitamin D has an important role in placental implantation and function through angiogenic, anti-inflammatory, and immunomodulatory effects. Some studies suggest low levels of vitamin D are associated with an increased risk of preeclampsia. In addition, primigravida is known to be more prone to preeclampsia than multigravidae. This study aims to determine the correlation between vitamin D 25-OH levels and the incidence of preeclampsia in primigravida mothers at the Obstetrics and Gynecology Polyclinic RSPAL dr. Ramelan Surabaya for the 2023-2025 period. Cross-sectional research was carried out at RSPAL dr. Ramelan Surabaya. A total of 66 primigravida mothers were selected by total sampling. The dependent variable is the occurrence of preeclampsia. The independent variable is the vitamin D 25-OH level. Data in the form of medical records of the Obstetrics and Gynecology Polyclinic RSPAL dr. Ramelan Surabaya for the 2023-2025 period. The data were analyzed by the Kendall's Tau-b test. The results of Kendall's Tau-b test showed that the age variable showed a weak positive association with the incidence of preeclampsia but was not statistically significant (τ = 0.195; p = 0.116). Body mass index (BMI) had a positive association with moderate strength and significant to the incidence of preeclampsia (τ = 0.334; p = 0.005), suggesting that an increase in BMI was associated with an increased incidence of preeclampsia. Mean Arterial Pressure (MAP) showed a very strong and significant positive association with the incidence of preeclampsia (τ = 1.000; p < 0.001), confirming the role of blood pressure as a factor strongly related to preeclampsia. Meanwhile, vitamin D 25-OH levels showed a weak and statistically insignificant positive association with the incidence of preeclampsia (τ = 0.217; p = 1,000). There is no correlation between vitamin D 25-OH levels and the incidence of preeclampsia in primigravida mothers at the Obstetrics and Gynecology Polyclinic RSPAL dr. Ramelan Surabaya for the 2023-2025 period.